The carbon footprint of transporting fresh seasonal fruit - Martin du Plessis; Joubert van Eeden; Leila Louise Goedhals-Gerber (Transportation Research Interdisciplinary Perspectives, 2025)
This article assesses the carbon footprint due to the transportation, handling and storage (i.e. distribution) of fresh fruit exported from South Africa to various international markets. This is the most detailed study of its kind on the scale and profile of the end-to-end distributional emissions of fresh fruit. The study also maps the typical logistical processes by which different types of fresh fruit are exported globally. It also summarises a novel 6-step emission standard. The study assessed all emission-generating distribution activities of packed fruit, from the gate of fruit-packing facility to the international destination port, including empty-vehicle movements and empty reefer-container repositioning. The distribution-specific carbon footprint for scenarios where ocean transport is used varies between 0.31 and 0.84 kg CO2e/kg of fruit. For air transportation, it can be approximately 11.35 kg CO2e/kg of fruit. Results show that the carbon footprint of the seven representative distribution scenarios depends on various factors.